Soteriological Studies About The Concept Of Choice God According To Romans 9:6-16 - Fernando Nababan; Widi Prasetyo; Ani Teguh Purwanto; Daniel Ari Wibowo (Theological Journal Kerugma, 2020)
God acts to choose a person or group and within a larger community, for a purpose or future of His own choosing. The main OT word for this word is bak-har (bak-har), which means to choose someone or something carefully, after carefully considering other possibilities. This word includes the mind, is very fond of the chosen thing, and sometimes receives pleasure from it. In the LXX and the NT the verb which corresponds to ba-khar is eklegomai. In ancient Greek this language was usually used in an active sense, and the biblical writers used it in a form meaning to choose for himself. (Hareomai) Haireomai, used of God's election in 2 Thess 2:13, and in Deut. 26:18 LXX, with the same meaning. The Hebrew verb (yada), meaning to know which is used for various ways of knowing, at least in the mind, containing and expressing love such as sexual relations, or confession on the part of one who believes in God is used in Gen. 18:19; Hos 13:5 concerning the election of God means knowing God in love. Likewise, the Greek word proginosko meaning “to know beforehand” is translated “He chose” in Romans 8:29.Election is a fully sovereign act of God; Allah is in no way obligated to choose anyone because everyone has lost his position before Allah. Even after Christ's death, God was still under no obligation to carry out salvation. Except that He had to keep the agreement He had made with Christ regarding the salvation of mankind. So, God's election is a fully sovereign act because there is no coercion from anyone.